Starting point 1979-1996 - Miyazaki, Hayao 1941- (VIZ Media, 2009)
Starting Point: 1979-1996 is a collection of essays, interviews, and memoir that go back to the roots of Miyazaki's childhood, the formulation of his theories of animation, and the founding of Studio Ghibli